Pleiotropic phenotype of transgenic Arabidopsis plants that produce the LOV domain of LOV KELCH PROTEIN2 (LKP2) - Takase, Tomoyuki; Miyazaki, Yuji; Yasuhara, Masahiro; Mitsui, Shunya; Kiyosue, Tomohiro (Plant Biotechnology, 2015)
LOV KELCH PROTEIN2 (LKP2) is a blue-light receptor protein composed of three functional domains: a light, oxygen, or voltage (LOV) domain, an F-box motif (F), and Kelch repeats. LKP2 is postulated to be a component of an SCF complex and function in ubiquitination of proteins that control the circadian clock and photoperiodic flowering. Transgenic Arabidopsis plants that produce LOV, F, or a combination of LOV and F fused to green fluorescent protein (named GL, GF, and GLF, respectively) were produced using constructs containing the Cauliflower mosaic virus 35S promoter. Under continuous white light, the circadian rhythms of control and GF plants were similar, whereas those of GL and GLF plants were shorter. Under continuous red light, the hypocotyl lengths of control and GF seedlings were similar, whereas that of GL seedlings was longer. Late flowering and down-regulation of CONSTANS and FLOWERING LOCUS T were observed in GL and GLF plants compared to GF and control plants under long-day conditions. These results suggest that the previously reported pleiotropic phenotype of LKP2-overproducing plants, which show altered circadian rhythm, hypocotyl elongation, and photoperiodic flowering, is not only due to the promotion of ubiquitination and subsequent degradation of substrate proteins of the SCFLKP2 complex but may also be due to the functional disruption of regulatory proteins that interact with LKP2 LOV.